PENINGKATAN PENGETAHUAN MASYARAKAT DI PANTI ASUHAN AL-HIDAYAH KECAMATAN KURANJI KOTA PADANG MELALUI EDUKASI TANAMAN OBAT KELUARGA DAN PEMBUATAN SIMPLISIA KELOR - Elidahanum Husni; Dira Hefni; Syofyan Syofyan; Bening Hawa Satia; Eko Bayu Saputro; Suryati Syafri (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Family Medicinal Plants (TOGA) are groups of plants traditionally cultivated in home gardens and used as sources of natural medicine. One of the widely utilized TOGA plants is Moringa leaves (Moringa oleifera Lam.), known for their high nutritional content and various pharmacological benefits. Research shows that Moringa leaves contain bioactive compounds such as flavonoids and phenolic acids, which support health benefits, including antioxidant and antimicrobial properties. This community service activity was conducted at Al-Hidayah Orphanage with the aim of enhancing the community’s understanding and skills in utilizing TOGA, particularly Moringa leaves, through herbal tea-making training. Using a qualitative approach, the activities included an initial survey, counseling, practical training, and evaluations through pre-test and post-test questionnaires to measure participants' knowledge improvement. The results showed a significant increase in participants’ understanding of TOGA benefits and Moringa leaf processing into herbal tea, with knowledge levels rising from an initial 16.7% to 91.3% after the training. This increase indicates that counseling and hands-on training effectively improved community awareness and skills. Additionally, the activity introduced the potential for developing herbal products from local plants, which could provide health benefits and economic opportunities through Moringa leaf-based herbal tea production. To sustain the program, further training is recommended to enhance participants’ proficiency in processing TOGA, especially as value-added herbal products. Collaboration with educational institutions is also suggested to expand research and development on TOGA products within the community.